The sustainable soul of the past. Learning from the present to regenerate outdated urban spaces - Antonella Falzetti; Giulio Minuto (Agathón)
There are many open spaces that today no longer connote themselves as community squares, places of sharing and belonging, unsuited to meet current expectations in terms of the psycho-physical well-being of the user and far from the logic of urban ecology. The places to which the contribution refers are often the result of a skilful design culture: they have contributed to the design of cities, to improve degraded areas, but they suffer from a lack of aptitude to project themselves into future transformative dynamics, resulting in spaces removed from the life cycle that their urban function requires today. By analysing the life cycle of these individual urban architectures, made before recent environmental policies, the question emerges as to their actual sustainability and resilience in the temporal progression of their operation. The essay aims to open a reflection on the opportunities for modification of these particular areas by acquiring from the NbS strategies specific and measured types of intervention in a perspective of adaptation in an eco-systemic key that is able to protect the architectural identity found.